A robust numerical method for granular hydrodynamics in three dimensions - Shakeri, Ali; Schiochet Nasato, Daniel; Müller, Patric; Torres Menendez, Harol; Pöschel, Thorsten (Journal of Fluid Mechanics, 2021)
Granular systems are of a discrete nature. Nevertheless, it can be advantageous to describe their dynamics by means of continuum mechanical methods. The numerical solution of the corresponding hydrodynamic equations is, however, difficult. Therefore, previous numerical simulations are typically geared towards highly specific systems and frequently restricted to two dimensions or mild driving conditions. Here, we present the first robust general simulation scheme for granular hydrodynamics in three dimensions which is not bound to the above limitations. The performance of the simulation scheme is demonstrated by means of three applications which have been proven as notoriously difficult for numerical hydrodynamic description. Although, by construction, our numerical method covers grain-inertia flows, the presented examples demonstrate that it produces reliable results even in the jammed or high density limit.
CRIS-Team Scopus Importer:2021-05-14
Keywords: granular media